2020
DOI: 10.3389/fneur.2020.546599
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography Mu Rhythm Changes and Decreased Spasticity After Repetitive Peripheral Magnetic Stimulation in Patients Following Stroke

Abstract: Background: Spasticity is common among patients with stroke. Repetitive peripheral magnetic stimulation (rPMS) is a painless and noninvasive therapy that is a promising approach to reducing spasticity. However, the central mechanism of this therapy remains unclear. Changes in cortical activity and decreased spasticity after rPMS intervention require further exploration. The aim of this study was to explore the electroencephalography (EEG) mu rhythm change and decrease in spasticity after rPMS interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Recently, event-related desynchronizations (ERDs) involved in the process of swallow have been reported in bilateral sensorimotor areas using magnetoencephalography (MEG) (Dziewas et al, 2003;Suntrup et al, 2013Suntrup et al, , 2014Suntrup et al, , 2015. Generally, ERDs are a decrease of the power in the alpha and beta frequency bands during voluntary movements when compared with that during the rest (nonmovement) (Pfurtscheller and Lopes da Silva, 1999;Li et al, 2018;Chen et al, 2020;Spadone et al, 2020;Xie et al, 2021). They are supposed to reflect cortical activities during voluntary movements (Pfurtscheller and Lopes da Silva, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, event-related desynchronizations (ERDs) involved in the process of swallow have been reported in bilateral sensorimotor areas using magnetoencephalography (MEG) (Dziewas et al, 2003;Suntrup et al, 2013Suntrup et al, , 2014Suntrup et al, , 2015. Generally, ERDs are a decrease of the power in the alpha and beta frequency bands during voluntary movements when compared with that during the rest (nonmovement) (Pfurtscheller and Lopes da Silva, 1999;Li et al, 2018;Chen et al, 2020;Spadone et al, 2020;Xie et al, 2021). They are supposed to reflect cortical activities during voluntary movements (Pfurtscheller and Lopes da Silva, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The overall risk of bias of the eight included studies are summarized in Figure 2, and the assessment results of the five domains and the overall bias for individual studies are shown in As no difference among the results of risk of bias for each outcome assessed in per study, the main outcome of the current review was selected to present in the Figure 3. Overall, one study (19) was assessed to be of high risk of bias and two (20,21) had some concerns, the others were at low risk of bias (22)(23)(24)(25)(26). Most of studies described a random sequence clearly, only one study (19) has high risk in randomization process.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…After a series of literature screening and qualification confirmation, eight RCTs (19)(20)(21)(22)(23)(24)(25)(26) were selected for systematic review, and six were presented in the form of a metaanalysis. Table 1 summarizes the characteristics of the included studies and patients with spastic paralysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…ALS patients with dysphagia showed less cortical activity in the bilateral sensorimotor areas during volitional self-paced swallowing, compared with healthy subjects in a previous magnetoencephalography (MEG) study using event-related desynchronization (ERD) (Teismann et al, 2011 ). ERD is a decrease in power spectral density in the alpha (10–12 Hz) and beta frequency bands (15–25 Hz) observed during voluntary movements and is thought to reflect motor-related cortical activity (Pfurtscheller and Lopes Da Silva, 1999 ; Li et al, 2018 ; Chen et al, 2020 ; Spadone et al, 2020 ; Xie et al, 2021 ). The ERDs within the beta frequency band (13–30 Hz) in bilateral sensorimotor areas were less prominent in patients with ALS, and the lower the ERD, the more severe the dysphagia they had (Teismann et al, 2011 ), suggesting that the reduced ERD reflected the disturbed function of the degenerated cortico-motoneurons.…”
Section: Introductionmentioning
confidence: 99%